Variation of Carrying Angle of Elbow in Relation to Age, Sex and Dominant Arm in Adolescent Bangladeshi Population (Journal of Chittagong Medical College Teachers' Association, 2022)
Background: Elbow carrying angle changes with skeletal growth and maturity, helps in carrying objects and keeps upper limb away from pelvis during movement. Variation of carrying angle value has been observed in relation to age, gender, and some selected anthropometric parameters. Present study was aimed to evaluate the carrying angle in normal adolescents of Bangladesh in relation to age, gender, and hand dominance.  Materials and methods: This cross-sectional observational study was conducted in the Department of Anatomy, Chittagong Medical College, Chattogram, upon 100 male and 100 female adolescents (10-19 years) by dividing them into two groups (Group A: 10-15 years, Group B: 16-19 years) and all were right hand dominant. Recorded data were analyzed by using SPSS version 25. For statistical analysis unpaired student’s ‘t’ test was done. p value was considered significant if it was